(untitled) (Research, Society and Development, 2021)
The concept of sexuality has changed over the years. It is one of the indicators of quality of life, an integral part of health and general well-being, not being restricted to the reproductive goal only, it strengthens affective relationships between people. Female sexuality has changed so that today we discuss more about previously unthinkable issues. However, there are still gaps in knowledge that must be studied to break paradigms and undo misconceptions. The present study carried out an integrative review of the literature on female sexual health. Original studies were obtained from the PubMed and SciELO databases using the descriptors: sexual dysfunction, female sexual health, women’s health, in Portuguese and English. The theme is extremely broad, covering physical, anatomical, social, biological, psycho-emotional issues as well as several external factors. The sexual life of women has a direct impact on their quality of life and because it is complex and individualized, it lacks the joint action of the various areas of knowledge and health.